Transforming Industry with Big Data: A Focus on Production Optimization - P Dubey, Amitkumar; Pranav S, Patel; Harsh A, Kansara; Dhameliya, Tisha; Vajani, Harsh; Tamakuwala, Nishtha; Gamit, Vipul (Journal of Neonatal Surgery, 2025)
Big Data is significantly reshaping various industries by driving smarter decision-making, fostering innovation, and enhancing operational efficiency. This paper investigates the transformative impact of Big Data across key sectors such as healthcare, finance, retail, and manufacturing. Using practical examples and current research, we demonstrate how organizations leverage Big Data to extract insights, streamline processes, improve customer engagement, and strengthen their market position. Additionally, we examine common challenges, including data security concerns and the growing demand for skilled professionals. This study offers a comprehensive perspective on how Big Data is influencing the evolution of global industries.